PENERAPAN MODEL KOOPERATIF NHT UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PASSING CONTROL SEPAKBOLA - I Wayan Edi Martawan .; I Wayan Artanayasa, S.Pd, M.Pd. .; I Made Satyawan, S.Pd. . (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan Undiksha, 2014)
Penelitian ini bertujuan meningkatkan aktivitas dan hasil belajar passing control sepakbola kaki bagian dalam melalui penerapan model pembelajaran kooperatif tipe NHT pada siswa kelas VIII B SMP Negeri 1 Susut tahun pelajaran 2013/2014. Penelitian ini adalah Penelitian Tindakan Kelas yang dilaksanakan dalam dua siklus. Subjek penelitian siswa kelas VIII B SMP Negeri 1 Susut, berjumlah 33 orang. Data menggunakan analisis statistik deskriptif. Hasil analisis data pada observasi awal aktivitas belajar passing sepakbola secara klasikal sebesar 5,93 (cukup aktif) meningkat pada siklus I menjadi 6,79 (Cukup Aktif) dan siklus II menikat sebesar 7,87 (Aktif). Sedangkan ketuntasan hasil belajar passing control sepakbola ( kaki bagian dalam ) secara klasikal pada observasi awal 64,89 (Kurang Baik), siklus I meningkat sebesar 69,48 (Cukup Baik), pada siklus II meningkat sebesar 84,08 (Baik). Berdasarkan analisis data disimpulkan bahwa aktivitas dan hasil belajar passing control sepakbola meningkat melalui penerapan model pembelajaran kooperatif tipe NHT pada siswa kelas VIII B SMP Negeri 1 Susut tahun pelajaran 2013/2014. Disarankan kepada guru penjasorkes dapat menggunakan model pembelajaran kooperatif tipe NHT karena dapat meningkatkan aktivitas dan hasil belajar passing control sepakbola ( kaki bagian dalam ) pada siswa.Kata Kunci : Kooperatif Tipe NHT, Aktivitas, Hasil Belajar, Passing Control Sepakbola. This study was aimed at improving students’ activity and achievement in learning football passing control technique of inner ankle through the use of NHT cooperative learning model toward students of class VIII B of SMP Negeri 1 Susut in the academic year 2013/2014. This research was design in the form of classroom based action research which was conducted in two cycles. The subject of this study was students of class VIII B of SMP Negeri 1 Susut which consists of 33 students. The data gained were analyzed using descriptive statistic analysis. The result of the data analysis showed that on primary observation the activity in classically learning of football passing control was about 5.93 (moderately active), then improved become 6.79 (moderately active) in the first cycle and it improved become 7.87 (active) in the second cycle. Meanwhile, the result of classically learning achievement of football passing control (inner ankle) was 64.89 (bad) on the primary observation, it improved become 69.48 (quite good) in the first cycle, and it improved become 84.08 (good) in the second cycle. Therefore, based on the data analysis, it can be concluded that the students’ activity and achievement in learning football passing control technique improved through the implementation of NHT cooperative learning model toward students of class VIII B of SMP Negeri 1 Susut in the academic year 2013/2014. It is suggested to the teacher to use NHT cooperative learning model as it can improve students’ activity and achievement in learning football passing control technique.keyword : NHT cooperative learning model, activity, achievement, football passing control technique